High- versus low-energy extracorporeal shock-wave therapy for myofascial pain syndrome of upper trapezius: A prospective randomized single blinded pilot study. Issue 28 (July 2018) - Park, Ki Deok; Lee, Woo Yong; Park, Min-ho; Ahn, Jae Ki; Park, Yongbum
Abstract: Background: To compare the efficacy of high- and low-energy extracorporeal shock wave therapy (ESWT) for patients with myofascial pain syndrome (MPS) of the upper trapezius. Methods: Thirty patients (3 men, 27 women) were randomly assigned to receive either high-energy ESWT (0.210 mJ/mm 2 ) or low-energy ESWT (0.068 mJ/mm 2 ). Both groups received 1500 pulses of ESWT once a week, for 2 weeks. Outcome measurement was assessed by verbal numeric pain scale (VNS), neck disability index (NDI), neck range of motion (ROM) (flexion, extension, rotation, lateral bending), and pressure threshold (PT). Statistical analysis was performed with significance level of P < .05. Results: No statistically significant differences of demographic and clinical characteristics existed between the 2 groups. VNS, NDI, neck ROM (rotation to sound side, lateral bending to affected side, lateral bending to sound side), and PT were improved in both groups. In contrast, statistically significant improvements in neck flexion and neck extension were observed only in the high-energy group. We also found significant differences in post-treatment NDI (4.20 ± 1.78 vs 6.47 ± 2.48) and post-treatment neck flexion ROM (65.47 ± 10.09 vs 55.93 ± 11.07) between high-energy and low-energy group. Conclusion: ESWT effectively improves VNS, NDI, neck ROM, and PT to patients with MPS of the upper trapezius. High-energy ESWT was more effective in improving NDI and neck flexion ROM compared to the low-energy ESWT, suggesting superiority in functional improvement. Further studies are required to specify the effect of ESWT by energy intensity.